ANALYSIS OF ANTIBACTERIAL ACTIVITY AND PHYTOCHEMICAL CONTENTS OF A RARE AND ENDEMIC LIANA (STROPHANTHUS WIGHTIANUS WALL. EX WIGHT) OF SOUTH INDIA - JOSEPH JOHN,; RAGI, P. R,; SUJANA, K. A.,; N. ANIL KUMAR, (International Journal of Pharma and Bio Sciences, 2012)
Antibacterial activity of cold water and ethanolic crude extracts of leaves of Strophanthus wightianus Wall. ex Wight was evaluated against Gram negative bacteria(Escherichia coli, Pseudomonas fluorescens, Klebsiella pneumoniae and Enterobacter aerogenes) and Gram positive bacteria (Staphylococcus aureus, Methicillin resistant Staphylococcus aureus, Streptococcus mutans and Bacillus subtilis). Methicillin resistant Staphylococcus aureus was the most sensitive strain of those tested with the cold water extract and Enterobacter aerogenes with the ethanolic extract of leaves Strophanthus wightianus Wall. ex Wight. Qualitative phytochemical analysis gave positive results for alkaloides, anthraquinones, lipids/fats, glycosides, phenols, carbohydrates, tannins, resins, reducing sugars,saponinsand flavonoids